Single and Multi-Metal Removal by an Environmental Mixed Bacterial Isolate - Sannasi, P.; Kader, J.; Othman, O.; Salmijah, S. (Wiley online library, 2008)
This paper reports the removal of metals from aqueous solution containing Cd(II), Cr(VI), Cu(II), Ni(II) and Pb(II) by a consortia culture (CC) comprising of environmental mixed bacterial culture. The metal removal capability of growing (active) and non‐growing (inactive) cell populations at initial total metal concentrations of 100 mg/l in single and multi‐metal systems were examined by determining percentage metal removal and specific metal uptakes (q0). The removal and uptake performance of consortia culture in the multi‐metal system was 23‐58% lower compared to the single metal system (p < 0.05). The efficiency of metal removal in the single metal systems were in the order of : Pb > Cu > Ni > Cd > Cr. Growing cells displayed higher metal removal and uptake capability compared to non‐growing cells for all metals tested except for Ni. For both growing and non‐growing populations, the order of metal removal was Pb > Cu > Ni > Cd > Cr. TEM studies showed that metals were deposited both intracellularly and extracellularly for the two cell populations. XRF analysis confirmed the identities of the sorbed metals.